Screening and Identification of Drought-Tolerant Genes in Tomato (Solanum lycopersicum L.) Based on RNA-Seq Analysis - Yue Ma; Yushan Li; Fan Wang; Quan Qing; Chengzhu Deng; Hao Wang; Yu Song (Plants)
Drought is one of the major abiotic stresses that inhibits plant growth and development. Therefore, it is critical to explore drought resistance genes in crops to obtain high-quality breeding materials. In this study, the drought-sensitive tomato line “FQ118” and the resistant line “FQ119” were treated with PEG-6000 and, at 0 h (CK), 6 h, 24 h, 36 h and 48 h, the plants were evaluated for growth and physiological indicators, and leaf tissues were collected for RNA-seq. The growth indicators (growth trend, dry and fresh weights above- and below-ground, etc.) and the antioxidant enzyme system reflect that “FQ119” has stronger drought tolerance. Through RNA-seq analysis, a total of 68,316 transcripts (37,908 genes) were obtained. The largest number of significant differentially expressed genes (DEGs) in the comparison of “FQ118” and “FQ119” was observed at 6 h and 48 h. KEGG analysis demonstrated the significant enrichment of certain pathways associated with drought stress, such as glycerolipid metabolism and galactose metabolism. Co-expression analysis revealed that 7 hub DEGs, including genes encoding a photosystem reaction center subunit protein, chlorophyll a-b binding protein, glyceraldehyde-3-phosphate dehydrogenase A (GAPDH), and others, were coenriched in both comparisons. In addition, three hub genes specific to the comparison during the 6-h processing stage, encoding oxygen-evolving enhancer protein 1, receptor-like serine/threonine-protein kinase and calcium-transporting ATPase, were identified. The above hub genes were related to plant resistance to drought stress, and RT‒qPCR verified that the overall magnitudes of the differences in expression between the two lines gradually increased over time. Virus-induced gene silencing (VIGS) experiments have demonstrated that GAPDH plays a relevant role in the drought resistance pathway. In addition, the differences in expression of 7 DEGs encoding transcription factors, including Dofs, WRKYs, MYBs, and MYCs, also tended to increase with increasing duration of drought treatment, as determined via qPCR. In summary, this study identified several valuable genes related to plant drought resistance by screening genes with differential transcription under drought stress. This in-depth gene mining may provide valuable references and resources for future breeding for drought resistance in tomato.